127:oral Withdrawing or withholding treatments in health care rationing decisions: an interview study. (28th April 2022) - Strand, Liam; Sandman, Lars; Tinghög, Gustav; Nedlund, Ann-Charlotte
Abstract : Objective: As more new- and high-cost treatments become available, there will be a greater need to decide whether the healthcare should withdraw and withhold these treatments from patients or not. When rationing health care, a commonly held view among ethicists is that there is no ethical difference between withdrawing or withholding medical treatments. This view has been questioned with reference to the discrepancy between active- and passive acts, or implicit promises, and does not generally seem to be supported among practitioners. Our objective was to explore physicians' and patient organization representatives' experiences- and perceptions of withdrawing and withholding treatments in a reimbursement priority setting. Methods: Fourteen semi-structured interviews were conducted with Swedish physicians and patient organization representatives from areas with high influx of new treatments, such as oncology, hematology, and neurological diseases, and were analyzed using a thematic analysis. Results: We identified eight different themes which demonstrate relevant factors when withdrawing/withholding treatment: patients' need of treatment, treatment effect in relation to alternative treatments, patient-professional communication, patient-professional relationship, healthcare responsibility, ethical values, professional support, and reimbursement system. Discussion: We find that practitioners perceive it to be a clinically and ethically significant difference between withdrawing and withholding treatments. We expand on the previous research as we find important ethical values among practitioners, such as perceiving it to be more important to make individual assessments for patients with previous access to treatments than to withdraw it to uphold patient equality. We also identify potential strategies to handle this situation practically. Such strategies could be to: have agreements between the physician and patient about potential future treatment withdrawals, evaluate the treatment's effect, and to provide guidelines on a national level.